About possibility of energy-efficient heating of cast iron in a close cupola forehearth - E. N. Gnezdov (Литьë и металлургия)
Therе is analyzed the possibility of heating of the melting product in the cupola forehearth due to combustion heat of natural gas, and also is given data on physical modeling of metal melt bursting by gas blushes and on experimental determination of gas stress in a forehearth.